Branched-chain amino acids as biomarkers in diabetes. Issue 1 (January 2016) - Giesbertz, Pieter; Daniel, Hannelore
Abstract : Purpose of review: Numerous human studies have consistently demonstrated that concentrations of branched-chain amino acids (BCAAs) in plasma and urine are associated with insulin resistance and have the quality to predict diabetes development. However, it is not known how altered BCAA levels link to insulin action and diabetes. This review addresses some recent findings in BCAA metabolism and discusses their role as reporter molecules of insulin sensitivity and diabetes and their possible contribution to disease progression. Recent findings: Changes in plasma and urine levels result mainly from altered metabolism in tissues and recent studies have thus focused on organ-specific changes in BCAA handling using animal models and human tissue samples. A decreased mitochondrial oxidation has been demonstrated in peripheral tissues and that was shown to be associated with an increased inflammatory tone and changes in adipokine levels (adiponectin and leptin). These changes appear already before insulin resistance is established. Key findings demonstrating the discordance between changes in BCAA and insulin resistance are derived from studies using insulin sensitizers and from data collected in patients undergoing Roux-en-Y bypass bariatric surgery. Intermediates derived from BCAA breakdown rather than BCAA itself were recently proposed to contribute to the development of insulin resistance and studies now explore the biomarker qualities of these metabolites. Summary: Understanding the mechanisms and putative causalities in the alterations in BCAA levels as found in obesity, metabolic syndrome and diabetes is crucial for any intervention options but also for the use of BCAA and derivatives as biomarkers in clinical routine.